KARAKTERISTIK PERUBAHAN POLA TEGANGAN DAN ARUS PEMBEBANAN MODUL SURYA DENGAN REFLEKTOR ALUMINIUM PADA SUDUT INKLINASI YANG BERVARIASI - Syarif, Habib; Wibawa, Unggul; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
Electricity is considered a vital energy source that is inseparable from the lives of communities, companies, and industries. This is evidenced by the significant increase in demand in Indonesia. Due to the increasing demand for energy, there is a need to transition to renewable energy. Indonesia has a potential of 442 GW of renewable energy, with the largest potential being solar energy at 207.8 GWp. Solar energy can be converted into electrical energy using solar modules. However, the efficiency of solar modules needs to be considered and improved, for example by installing reflectors positioned at an appropriate angle of inclination. The research method used was an experiment involving the installation of aluminum reflectors and variations in inclination angles. The reflectors were installed on one side or both sides, while the inclination angles varied between 30°, 45°, 60°, 75°, and 90°. The solar module used was a 20WP polycrystalline type connected to 13 units of 1.5-Watt DC LED lamps, each with its own switch. Voltage, current, and output power data are presented in line graphs, which yield regression equations that facilitate data analysis. The research findings consist of voltage, current, sunlight intensity, and temperature data provided in a table. The obtained data was analyzed to produce other quantities such as output power and input radiation. Voltage, current, and output power data are presented in line graphs, which yield regression equations that facilitate data analysis. Additionally, the top ten output power data will be displayed in a bar graph. The operation of installing a reflector has a significant impact on the voltage and current values at inclination angles of 60˚ and 75˚. The highest output power is achieved when using two aluminum reflectors, an inclination angle of 60˚, and a load of 19.5 Watt. Keywords: solar module, voltage, current, reflector, output power.